YouTuber and Googlepreneur: Review of the Contemporary Fiqh of Zakah - Mubarok, Muhammad Sultan; Abadi, Muhammad Taufiq (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2020)
The industrial revolution 4.0 brings opportunities and challenges for zakat management institutions. YouTuber and Googlepreneur are part of the effects of changing times, which has the potential to generate revenue. The purpose of this study is to discuss Islamic jurisprudential law regarding zakat Youtuber and googlepreneur, as well as how to calculate nishab. The study shows that YouTubers and Googlepreneur are required to pay zakat because it belongs to the profession affected by zakat. The method of calculating zakat is based on three approaches, namely (a) referring to zakat of gold, silver, and trade, provided that the calculation of 85 grams of gold (20 dinars) or 595 grams of silver (200 dirhams) with a tithe content of 2.5% and time to spending once a year, (b) expressed by agricultural alms, with the provisions of aishq five ausaq (harvest 653 kg), the level is 5% and issued every income or salary, (c) qyas shahbah or analogous to two things at once, with the provisions of nishab five ausaq (653 kg of harvest) and released when receiving 2.5%.